2004
DOI: 10.1016/j.engfailanal.2003.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of low cycle fatigue in AlMgSi aluminium alloys

Abstract: In this study low-cycle fatigue tests were performed in two AlMgSi aluminium alloys with different chemical composition, namely 6082-T6 and 6060-T6 alloys, using standard round specimens and tube specimens, respectively. The tests were undertaken in strain control with a strain ratio R e ¼ À1. The cyclic stress-strain curves were determined using one specimen for each imposed strain level. The low-cycle fatigue results are used for the characterisation of the cyclic plastic response and the fatigue live of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 6 publications
3
60
0
12
Order By: Relevance
“…This convergence and divergence was agreed with tensile properties. The transition life (NT) is defined as the life where the total strain amplitude consists of equal elastic and plastic components, this imply, the life at which the elastic and plastic curves intersect (Haji, 2010;Borrego et al, 2004;Fenga et al 2010). The transition life was found to be the highest for O-condition, because it is being the less hardening behavior among other conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This convergence and divergence was agreed with tensile properties. The transition life (NT) is defined as the life where the total strain amplitude consists of equal elastic and plastic components, this imply, the life at which the elastic and plastic curves intersect (Haji, 2010;Borrego et al, 2004;Fenga et al 2010). The transition life was found to be the highest for O-condition, because it is being the less hardening behavior among other conditions.…”
Section: Resultsmentioning
confidence: 99%
“…To allow this prediction, complete information about the response and behavior of the material subjected to cyclic loading is necessary (Haji, 2010;Kwon, Song, Shin, & Kwun, 2010). Borrego, Abreu, Costa and Ferreira (2004) studied low-cycle fatigue of two AlMgSi aluminum alloys AA6082-T6 and AA6060-T6 alloys. They were concluded that AA6060-T6 exhibits nearly ideal Masing behavior, while alloy AA6082-T6 presents significant deviations from the Masing model.…”
Section: Introductionmentioning
confidence: 99%
“…The monotonic strength and elastic properties of the 6061-T651 aluminium alloy are presented in Table 2. Table 2 also includes the properties obtained by Moreira et al (2008), for the 6061-T6 aluminium alloy, and by Borrego et al (2004), for the 6082-T6 aluminium alloy, for comparison purposes. In general, the three materials show comparable properties.…”
Section: Experimental Strain-life Datamentioning
confidence: 99%
“…Table 3 summarizes the fatigue properties of the 6061-T651 aluminium alloy as well as the cyclic elastoplastic constants. Also, the properties obtained by Borrego et al (2004), for the 6062-T6 aluminium alloy, and Chung & Abel (1988), for the 6061-T6 aluminium alloy, are included for comparison purposes. The 6061-T651 aluminium alloy shows significantly higher fatigue ductility than the other aluminium alloys.…”
Section: Experimental Strain-life Datamentioning
confidence: 99%
“…The material properties used in the hardening rule, based on cyclic hardening, were obtained by the Ramberg Osgood relationship. The hardening coefficient H= 443 MPa and the hardening exponent n'= 0.064 were obtained from Borrego et al (41,42). The crack was grown in the numerical models by applying two load cycles and releasing the crack tip node just after the maximum load on the second load cycle.…”
Section: Numerical Proceduresmentioning
confidence: 99%